2022
DOI: 10.24018/ejfood.2022.4.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Radish in Aonla based Multistoried Agroforestry System

Abstract: An experiment was conducted in a 19-years old aonla orchard from October 2019 to January 2020 at the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) research farm to determine the performance of different radish varieties in aonla based multistoried agroforestry systems. The study consisted of two factors viz. four agroforestry systems (aonla + carambola, aonla + lemon, aonla only, and open field) and four radish varieties (BU mula-1, BARI Mula-1, BARI Mula-2 and Rocky 45) laid out in a two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Average light intensity was higher in T3 treatment ( dragon fruit sole) 1503.36 µ mol m -2 s -1 than T2 treatment ( aonla + dragon fruit) 1181.70 µ mol m -2 s -1 and lower light intensity was found in T1 treatment (multistoried system) 1128.22 µ mol m -2 s -1 (Fig 2). Similar results were observed by [10], [13] and [14] that was shading by upper storied species was responsible for reducing the photosynthetically active radiation which controls production of photosynthates, dry matter partitioning and fruit yield.…”
Section: B Photosynthetically Active Radiation (Par) Distributionsupporting
confidence: 86%
See 1 more Smart Citation
“…Average light intensity was higher in T3 treatment ( dragon fruit sole) 1503.36 µ mol m -2 s -1 than T2 treatment ( aonla + dragon fruit) 1181.70 µ mol m -2 s -1 and lower light intensity was found in T1 treatment (multistoried system) 1128.22 µ mol m -2 s -1 (Fig 2). Similar results were observed by [10], [13] and [14] that was shading by upper storied species was responsible for reducing the photosynthetically active radiation which controls production of photosynthates, dry matter partitioning and fruit yield.…”
Section: B Photosynthetically Active Radiation (Par) Distributionsupporting
confidence: 86%
“…Heavy rainfall used to occur during the months from May to September and scanty rainfall during rest of the year. The soil of the experimental field was originally shallow red brown terrace [8], [9] of Madhupur Tract (AEZ 28) under Salna series [10]. Initial soil and status of different treatments was as follows:…”
Section: B Climate Weather and Soilmentioning
confidence: 99%
“…Additionally, when a plant is in the shade, it releases the hormone auxin, which causes it to display apical dominance and raise the plant's height so that it can capture more light [20]. Similar result was observed by [21] in cotton, [22] in okra, [13] in dragon fruit, and [18] in cauliflower.…”
Section: B Plant Heightsupporting
confidence: 77%
“…The extent of light interception by tree crowns and competition for light are also limiting factors for the success of component crops in a multistory agroforestry system. It is reported that, agroforestry systems received different levels of light due to the different sizes and shapes of the overstory canopy" [25]. The research revealed that plant height, and leaf number was the highest in the agroforestry system.…”
Section: Discussionmentioning
confidence: 99%